Tom Clancy Code of honor [large type] - Cameron, Marc; Clancy, Tom, 1947-2013 (Clancy, Tom, 1947-2013. Jack Ryan novel, 2019)
As President of the United States, Jack Ryan has faced many challenges, but none have been as personal as this and never has he been this helpless in the face of evil in the latest entry in Tom Clancy's series. Father Pat West, S.J. was a buddy of the young Jack Ryan when they were both undergraduates at Loyola University. Father West left a comfortable job in the philosophy department at Georgetown to work with the poor in Indonesia. Now he's been arrested and accused of blasphemy against Islam. President Ryan is desperate to rescue his old friend, but he can't move officially against the Indonesians. Instead, he relies on the Campus team to find out who is framing the priest. There's one other twist to the story. President Ryan discovers a voicemail on his private cell phone from the priest warning about a coming attack against America.